The role of entrepreneurs in firm-level innovation: Joint effects of positive affect, creativity, and environmental dynamism - Baron, Robert A.; Tang, Jintong (Journal of Business Venturing, 2011)
Innovation is often a crucial ingredient in new venture success but at present, we know relatively little about the role of individual entrepreneurs in encouraging its occurrence. The present research addressed this issue by investigating the joint effects, on firm-level innovation, of two variables pertaining to entrepreneurs (their creativity and positive affect) and a key environmental variable (environmental dynamism). Although it has been predicted that affect plays an important role in entrepreneurship [Baron, R. A., 2008. The role of affect in the entrepreneurial process. Academy of Management Review 33(2), 328–340.], relatively little empirical evidence on its effects has been obtained to date (e.g., [Foo, M.D. In press. Emotions and entrepreneurial opportunity evaluation. Entrepreneurship Theory and Practice.]). Further, although the link between creativity and innovation has been described in past literature [Amabile, T.M., 1988. A model or creativity and innovation in organizations. In B.M. Staw and L.L. Cummings (Ed.)., Research in organizational behavior 10, 123–167.], direct evidence for its existence is currently lacking. Findings of the present research indicate that positive affect among founding entrepreneurs is significantly related to their creativity and that creativity, in turn, is positively related to firm-level innovation. Both of these relationships are moderated by environmental dynamism, being stronger in highly dynamic than stable environments.